Data from: Reproduction as a bottleneck to treeline advance across the circumarctic forest tundra ecotone ... - Brown, Carissa D.; Dufour-Tremblay, Geneviève; Jameson, Ryan G.; Mamet, Steven D.; Trant, Andrew J.; Walker, Xanthe J.; Boudraeu, Stéphane; Harper, Karen A.; Henry, Greg H.R.; Hermanutz, Luise; Hofgaard, Annika; Isaeva, Ludmila; et al. (Dryad, 2018)
The fundamental niche of many species is shifting with climate change, especially in sub-arctic ecosystems with pronounced recent warming. Ongoing warming in sub-arctic regions should lessen environmental constraints on tree growth and reproduction, leading to increased success of trees colonising tundra. Nevertheless, variable responses of treeline ecotones have been documented in association with warming temperatures. One explanation for time lags between increasingly favourable environmental conditions and treeline ecotone movement is reproductive limitations caused by low seed availability. Our objective was to assess the reproductive constraints of the dominant tree species at the treeline ecotone in the circumpolar north. We sampled reproductive structures of trees (cones and catkins) and stand attributes across circumarctic treeline ecotones. We used generalized linear mixed models to estimate the sensitivity of seed production and the availability of viable seed to regional climate, stand structure, ... : Treeline Reproduction DataData from Brown et al. Ecography reproductive potential at treeline. Data from circumarctic treeline stands. Seed production and viability of available seeds.Brown_etal_Ecography_TreelineReproData_Dryad.xlsx ...